1970
DOI: 10.1115/1.3449629
|View full text |Cite
|
Sign up to set email alerts
|

Laminar Free Convection From Vertical Cylinders With Uniform Heat Flux

Abstract: The boundary-layer analysis of free-convection heat transfer from a vertical cylinder with uniform heat flux at its surface is made. The transformed ordinary coupled equations form a two-parameter system (ηw and Pr). The two search type of equations is solved using an iterative scheme developed for the isothermal case. Numerical solutions obtained for parametric values of Pr and ηw indicate that the cylinders can be classified as short cylinders, long cylinders, and wires. Heat transfer correlations are presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0
3

Year Published

1974
1974
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(7 citation statements)
references
References 0 publications
1
3
0
3
Order By: Relevance
“…Both the total and convective NusseIt numbers increased proportionally to the Rayleigh number raised to one-fourth power. The correlation of the data in terms of NUD and RaD made it possible to compare the present results with the heat transfer correlation for a vertical heated cylinder of a diameter D in an infinite media [19]. The plot embedded in the upper right hand corner of Figure 8 shows that the values of the coefficient CD for very large annulus ratios approach the value of 0.6 which had been reported for a heated vertical cylinder in infinite media [19].…”
Section: 0":1------------------------supporting
confidence: 51%
See 1 more Smart Citation
“…Both the total and convective NusseIt numbers increased proportionally to the Rayleigh number raised to one-fourth power. The correlation of the data in terms of NUD and RaD made it possible to compare the present results with the heat transfer correlation for a vertical heated cylinder of a diameter D in an infinite media [19]. The plot embedded in the upper right hand corner of Figure 8 shows that the values of the coefficient CD for very large annulus ratios approach the value of 0.6 which had been reported for a heated vertical cylinder in infinite media [19].…”
Section: 0":1------------------------supporting
confidence: 51%
“…The correlation of the data in terms of NUD and RaD made it possible to compare the present results with the heat transfer correlation for a vertical heated cylinder of a diameter D in an infinite media [19]. The plot embedded in the upper right hand corner of Figure 8 shows that the values of the coefficient CD for very large annulus ratios approach the value of 0.6 which had been reported for a heated vertical cylinder in infinite media [19]. These results are consistent with those of Prasad and Kulacki [8,9,10] and Prasad [20]; they have fully established …”
Section: 0":1------------------------mentioning
confidence: 93%
“…Laminar free and mixed convection boundary-layer flow along a static vertical cylinder has been studied by many investigators, see, for example, Nagendra et al [7], Chen and Mucoglu [8], Mucoglu and Chen [9], Lee et al [10], Mahmood and Merkin [11]. However, there are only a relatively few studies on the boundarylayer flow past a moving cylinder, Karnis and Pechoc [12], Lin and Shih [13,14], Takhar et al [15].…”
Section: Introductionmentioning
confidence: 96%
“…Goldstein and Briggs [2] presented an analysis of the transient free convective flow past vertical flat plate and circular cylinder to a surrounding initially quiescent fluid by employing Laplace transform technique. Nagendra et al [3] presented a boundary layer analysis of free convection heat transfer from a vertical cylinder with uniform heat flux at its surface. An experimental and analytical study is reported by Evas et al [4] for transient natural convection in a vertical cylinder.…”
Section: Introductionmentioning
confidence: 99%